Plastic waste management through biological methods: an approach towards sustainable development (Bioresearch Communications, 2024)
At present, the massive plastic pollution load into the environment has become an alarming issue in the world. Plastic wastes enter into the food chain through different ways and can cause serious health issues in aquatic animals and humans besides environmental pollution. Several techniques, including adsorption, coagulation, photocatalysis, and microbial degradation, as well as approaches such as reduction, reuse, and recycling, are currently popular. These techniques vary in their efficiency and the way they interact. Additionally, this review emphasizes the significant benefits and difficulties linked to these methods and strategies in order to comprehend the process of choosing viable paths toward a sustainable future. However, besides reducing plastic waste in the ecosystem, other alternative avenues have also been recently investigated to convert plastic wastes into value-added products for the circular economy. This review paper provides an overview of the currently documented methods and strategies focusing on the biological approaches used for the elimination of plastic trash and bioplastic development approaches. Furthermore, it is crucial to gain a comprehension of the key variables that must be highlighted while contemplating various methods and possibilities for bioplastic production, or insights into the potential utilization of these trashes as valuable resources or converting the plastic wastes into electricity, and transforming it into fuel. This review aims to offer readers a thorough summary of the current state of research about tactics and strategies to address the worldwide problem of plastic pollution.Bioresearch Commu. 10(2): 1597-1608, 2024 (July)